2009
DOI: 10.1080/15332640903327583
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Spirituality in a Sample of Men and Women in Diverse Substance Abuse Treatment Settings: Implications for Practitioners

Abstract: There has been a growing recognition of the need to understand the role of spirituality in ethnically diverse populations in social work and other helping professions. Although researchers are increasingly examining ethnic variations in prevalence rates, treatment utilization, and treatment outcomes for individuals with substance abuse problems, limited research attention has been focused on the relationship between spirituality and ethnicity in the substance abuse field. The current study addressed this gap i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Since its development, the ESI and the dimensional model have been used by MacDonald and others to examine the relation of spirituality to numerous aspects of functioning, including health, psychopathology, substance use, sexual orientation, boredom proneness, anomalous temporal lobe signs, trait personality, empathy, altruism, and work and organizational values and behavior (e.g., Adamovova and Strizenec, 2004;Affeldt and MacDonald, 2010;Bliss, 2009Bliss, , 2011Boyd-Starke et al, 2011;Huber and MacDonald, 2012;MacDonald and Holland, 2002a, 2002b, 2003. As importantly, they have served as the basis for theory development and/or validation in the creation of new models and measures of spirituality and religiosity (e.g., Kassab and MacDonald, 2011;MacDonald, 2009MacDonald, , 2011aMacDonald and Holland, 2002c;Saucier and Skrzypinska, 2006).…”
Section: Research Using Macdonald's Model and Measurementioning
confidence: 99%
“…Since its development, the ESI and the dimensional model have been used by MacDonald and others to examine the relation of spirituality to numerous aspects of functioning, including health, psychopathology, substance use, sexual orientation, boredom proneness, anomalous temporal lobe signs, trait personality, empathy, altruism, and work and organizational values and behavior (e.g., Adamovova and Strizenec, 2004;Affeldt and MacDonald, 2010;Bliss, 2009Bliss, , 2011Boyd-Starke et al, 2011;Huber and MacDonald, 2012;MacDonald and Holland, 2002a, 2002b, 2003. As importantly, they have served as the basis for theory development and/or validation in the creation of new models and measures of spirituality and religiosity (e.g., Kassab and MacDonald, 2011;MacDonald, 2009MacDonald, , 2011aMacDonald and Holland, 2002c;Saucier and Skrzypinska, 2006).…”
Section: Research Using Macdonald's Model and Measurementioning
confidence: 99%
“…Taylor et al (2009) found within ethnically diverse groups, representative of African Americans, Caribbean blacks, and non-Hispanic whites, significant differences in the way the different ethnic groups experience and view spirituality and the relation of spirituality with religion, even between the two groups of blacks. When comparing ethnically diverse groups in terms of multiple aspects of spirituality, (Bliss 2009) found significant differences in how African Americans, whites, and Hispanics view aspects of spirituality. The same trend was found in a study conducted on white and black students (Paredes-Collins and Collins 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is much evidence that the experience and expression of spirituality differs according to diversity aspects such as gender (Briggs and Dixon 2013;Keshet and Simchai 2014;Vosloo, Wissing and Temane 2009) or ethnic and race groups (Archibald 2010;Lewis 2015;Sharma Rastogi and Garg, 2013). In addition, spirituality tends to moderate several outcome behaviors in people from diverse groups (Bliss 2009); Harvey and Martinko 2009;Taylor, Chatters and Jackson 2009), and leads to positive work outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Social work, as well as other helping professions, has begun to include spirituality as a component of person-in-environment assessment (Bliss, 2009). Furthermore, the Joint Commission on Accreditation of Healthcare Organizations, the largest and most influential healthcare accrediting body in the United States, revised its standards in 2001 to require that spirituality be assessed in a variety of health care settings, including some types of behavioral health care organizations such as those that provide alcohol and drug dependence services (Hodge, 2006;Bliss, 2009 Fortunately, there is a growing research base that highlights the role of spirituality in improving treatment outcomes. In a literature review of 44 empirical studies on various aspects of the relationship between spirituality and alcohol and drug dependence, Bliss (2007) noted that 31 of these articles examined spiritual variables as components of the recovery process.…”
mentioning
confidence: 99%